regional urban-rural differnttials of the educational tmpact on ferttljty in egypt - mahgoub, youssef (Cairo Demographic Center, 1992)
It will be of particular interest to policy makers, government officials, researchers, and economists interested in fostering inclusive economic growth in the countries of the region and their deeper integration into the global economy."--BOOK JACKET.